The improvement of civil aviation in Turkey and its contribution to the Turkish economy - Seneger, İdris (My University, 2014)
Türk havacılık sektöründe son 30 yılda önemli derecede büyüme yaşanmıştır. Bu büyüme 1983 yılındaki sektördeki serbestleşme ile başlayıp 1990’lı yıllarda yeni havalimanlarının açılması, askeri havalimanlarının sivil kullanıma açılması, altyapının geliştirilmesi gibi kapasite ve kullanımı arttırıcı etkilerle büyüme devam etmiştir. 2003 yılında çıkarılan yeni yasa ile birlikte özel şirketlerin iç hat uçuşlarına daha rahat girebilmesiyle rekabet ortamına geçilerek havacılık sektöründeki büyümede büyük bir sıçrama gözlenmiştir. Günümüzde Türk sivil hava taşımacılığı piyasası yeni kurallara göre yeniden şekillenmiş ve belirli bir olgunluğa erişmiştir. Bu tezde, Türkiye’de sivil havacılığın tarihsel gelişimi ve Türkiye ekonomisine olan direkt katkısı; erişilebilirlik, sürdürülebilirlik, istihdam, hava kargo taşımacılığı, turizm gibi temel konular üzerinde incelenmeye çalışılmıştır.

There has been a great development in Turkish civil aviation in the last 30 years. This development started with the liberalization within the sector in 1983 and continued with increasing capacity and utilization ways such as launching new airports, opening of military airports to civilian transportation and developing infrastructure in 1990s. A competition environment was created when private companies participated in domestic flights with the law enacted in 2003 and thus it has been observed an increase in the development of civil aviation sector. Today, Turkish air transportation marketplace has been reshaped with new rules and it has reached a certain level. In this thesis, historical evolution of civil aviation in Turkey is summarized and its direct influence on Turkish economy are studied on basic issues such as connectivity, sustainability, employment, air cargo development and tourism development.
Keywords: Askeri Taşımacılık; Erişilebilirlik; Hava Kargo Taşımacılığı; Hava Taşımacılığı; Hava Taşımacılığı, Türkiye; İktisat; İstihdam; Sivil Taşımacılık, Türkiye; Sürdürülebilirlik; Turizm